1996
DOI: 10.1210/endo.137.10.8828495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitogens on androgen receptor-mediated transactivation.

Abstract: The effects of mitogens and agents affecting tyrosine phosphorylation signaling on androgen-regulated transcription were investigated. CV-1 and HeLa cells were cotransfected with an androgen receptor (AR) expression vector and an androgen-responsive chloramphenicol acetyltransferase (CAT) reporter gene driven by the mouse mammary tumor virus promoter. Growth factors [epidermal growth factor (EGF) and insulin-like growth factor I] that activate receptor tyrosine kinases, an inhibitor of phosphotyrosine phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…[58][59][60] Therefore, SHP-1 could have an important role in modulation of the signaling pathways initiated by growth factors and/or cytokines in the prostate. Further studies are needed to determine the exact role and the pathways involved in SHP-1 signaling in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60] Therefore, SHP-1 could have an important role in modulation of the signaling pathways initiated by growth factors and/or cytokines in the prostate. Further studies are needed to determine the exact role and the pathways involved in SHP-1 signaling in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include, the ability of tyrosine kinase-activating growth factors, such as EGF and IGF-1, to activate or potentiate the transactivation functions of androgen, progesterone, estrogen and GRs [30][31][32][33]. In their work with the androgen receptor, Reinikainen et al [33] showed that androgen-dependent transcription activity in CV-1 and Hela cells could be increased, not only by EGF and IGF-1, but also by vanadate. Interestingly, although EGF did not alter the hormone-binding response of this receptor, vanadate treatment caused a significant reduction in this function that was reversible by treatment with genistein.…”
Section: Discussionmentioning
confidence: 99%
“…This may possibly occur via the activation of MAPK and/or JNK pathways Lev et al, 1995). There may be interactions between steroid-activated signal transduction pathways and polypeptide growth factoractivated pathways, as demonstrated for estrogen receptors (Culing et al, 1995;Reinikainen et al, 1996). In the prostate, Pyk2 could be involved in the interac- …”
Section: Discussionmentioning
confidence: 99%